2011
DOI: 10.1371/journal.pone.0026922
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Cooperative Behaviour within a Single City

Abstract: Human cooperative behaviour, as assayed by decisions in experimental economic dilemmas such as the Dictator Game, is variable across human populations. Within-population variation has been less well studied, especially within industrial societies. Moreover, little is known about the extent to which community-level variation in Dictator Game behaviour relates to community-level variation in real-world social behaviour. We chose two neighbourhoods of the city of Newcastle upon Tyne that were similar in most rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
141
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 36 publications
16
141
2
Order By: Relevance
“…within the same city cooperate [9] and retaliate [42] at different rates; the same is true for people from different villages within the same broad cultural group [8]. These within-population individual differences are, in principle, amenable to individual-level explanations, as the architects of the cultural group selection approaches to cooperation readily concede [5,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…within the same city cooperate [9] and retaliate [42] at different rates; the same is true for people from different villages within the same broad cultural group [8]. These within-population individual differences are, in principle, amenable to individual-level explanations, as the architects of the cultural group selection approaches to cooperation readily concede [5,43].…”
Section: Discussionmentioning
confidence: 99%
“…Norms for cooperating, and for punishing defectors, it is argued, proliferate because they suit people for life in large societies in which social and economic life increasingly incorporates non-kin and interactions that cannot be stabilized through direct reciprocity [7]. The sufficiency of this theoretical approach, however, is called into question by recent evidence that the variation among populations within a single culture [8], and even neighbourhoods within the same city [9], is as substantial as is the variance between cultures-not to mention the substantial individual differences among individuals from the same subject pools [10]. Thus, other theories for these individual differences merit consideration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Nettle et al [39] compared cooperative behaviours in two neighbourhoods in the same British city (Newcastle-upon-Tyne) that differed in socio-economic status (SES). Using a dictator game, Nettle et al found that participants living in the harsher neighbourhood gave significantly less than participants living in the more affluent neighbourhood.…”
Section: Investing In Cooperation: Extended Prosocialitymentioning
confidence: 99%
“…One possible explanation for this finding is that participants with lower greenness may be likelier to live in deprived neighborhoods. Previous studies [47,48] have found that living in deprived neighborhoods was associated with lower social capital (in terms of trusting neighbors, helping each other out, etc. ), which may add to the observed result in our study.…”
Section: Discussionmentioning
confidence: 95%